Two opposite abilities of the infectious bronchitis virus helicase Nsp13: separating the duplex and promoting the annealing of single-stranded nucleic acid - Wu, Chengcheng; Tao, Lihan; Li, Haiqin; Huang, Cong; Zeng, Yanbing (Frontiers in Veterinary Science, 2025)
Genome replication is a key step in the coronavirus life cycle and requires the involvement of a range of virally encoded non-structural proteins. The non-structural protein 13 (Nsp13) of coronaviruses is a highly conserved helicase and is considered an ideal drug target. However, the activity characteristics of the helicase Nsp13 of the infectious bronchitis virus (IBV) remain unclear. In this study, we expressed and biochemically characterized the purified recombinant IBV Nsp13 and found that IBV Nsp13 was able to unwind duplex substrates in a 5′-to-3′ direction by using the energy from the hydrolysis of all nucleotide triphosphate (NTP) and deoxyribonucleoside triphosphate (dNTP). We also explored the substrate selectivity and influencing factors of the unwinding activity of IBV Nsp13. The nucleic acid continuity of the loading strand was essential for Nsp13 to unwind duplex substrates. In addition, we first demonstrated that IBV helicase Nsp13 also had an annealing activity to promote two single-stranded nucleic acids to form a double-stranded nucleic acid. Biochemical analysis of the unwinding and annealing activities of IBV Nsp13 was helpful for deeply revealing the replication mechanism of coronavirus and the development of antiviral drugs.